Reconceptualizar la ampliación de la perspectiva temporal futura mediante el pensamiento futuro episódico - Husman, Jenefer (2025)
Future time perspective extension is an individual's perception of the psychological distance between future goals. The concept of extension can be expanded to include how far into the future an individual habitual time space extends and the diffusion of goals within that time space. This alignment and distance may be related to the individual episodic future thinking, the pre-experiencing of future events. Research in FTP and EFT are typically siloed; considering both approaches to future thinking provides not only greater insight into the two constructs but may also provide avenues for developing interventions. Participants in this study (n = 13) were recruited from a scholarship program designed to provide them with financial support as they progress from community college to high-wage careers in science and engineering. Students were transitioning from two-year programs at local community colleges to science degree programs at a large four-year research university. Students’ narratives of their future lives were collected using an interview format, participants also completed a digital survey to quantitatively measure their future time perspective. Qualitative data were analyzed using a deductive thematic analytic approach and a content analytic approach. Students’ profiles differed in extension (how far into the future students' project) and diffusion (how many potential future careers are considered). Findings suggest that students with more extended, vivid, and specific career narratives. have higher career commitment and self-efficacy. The study concludes that understanding the intersection of FTPE and EFT can inform educational interventions to support students in visualizing and planning for their careers, particularly in science and engineering fields.